2017
DOI: 10.1063/1.4984841
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between domain structures and polarization switching in hybrid improper ferroelectric Ca3(Mn,Ti)2O7

Abstract: Ca3Mn2O7 and Ca3Ti2O7 have been proposed as the prototypical hybrid improper ferroelectrics (HIFs), and a significant magnetoelectric (ME) coupling in magnetic Ca3Mn2O7 is, in fact, reported theoretically and experimentally. Although the switchability of polarization is confirmed in Ca3Ti2O7 and other non-magnetic HIFs, there is no report of switchable polarization in the isostructural Ca3Mn2O7. We constructed the phase diagram of Ca3Mn2-xTixO7 through our systematic study of a series of single crystalline Ca3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 22 publications
4
56
0
Order By: Relevance
“…The black circles show the data previously reported for Ca3 Ti 2 O 7 , 32 Sr 3 Zr 2 O 7,37 and Ca 3 Mn 2 O 7 40. The squares indicate the reported data for solidsolution systems, (Ca,Sr) 3 Ti 2 O 734 and Ca 3 (Ti,Mn) 2 O 7 32,35. function of t. T C is found to monotonically increase with decreasing t. Because of the ubiquity of t in characterizing perovskite units, we can extend the compositional range to other n = 2 RP ferroelectrics.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The black circles show the data previously reported for Ca3 Ti 2 O 7 , 32 Sr 3 Zr 2 O 7,37 and Ca 3 Mn 2 O 7 40. The squares indicate the reported data for solidsolution systems, (Ca,Sr) 3 Ti 2 O 734 and Ca 3 (Ti,Mn) 2 O 7 32,35. function of t. T C is found to monotonically increase with decreasing t. Because of the ubiquity of t in characterizing perovskite units, we can extend the compositional range to other n = 2 RP ferroelectrics.…”
mentioning
confidence: 90%
“…A non-distorted structure forms with t ~ 1.0, whereas for smaller t values (0.8 < t < 1.0), the A-site cation is too small for its site resulting in a low-symmetry structure with rotated and/or tilted BO 6 octahedra. Figure 10 plots the T C s of (Sr 1−x Ca x ) 3 Sn 2 O 7 (x = 0, 0.1, and 0.2) system as a 34 , and Ca 3 (Ti,Mn) 2 O 7 32,35 . In the suite of fifteen different A 3 B 2 O 7 ferroelectrics, T C s range from below room temperature (~ 280 K) to about 1100 K. We find a linear relationship between the T C and t (Figure 10).…”
Section: Universal Relationship Of Curie Temperatures and Tolerance Fmentioning
confidence: 99%
See 1 more Smart Citation
“…A reasonable explanation is the weak SOI associated with the 3d Mn ion compared to 5d-electron iridates [39]. Although small, the unambiguous existence of the canted moment in conjunction with the soft oxygen octahedral tilt mode offers a feasible strategy to achieve magnetoelectricity control in this layered perovskite, i.e., switching the direction of net moment with electric field [18,40].…”
Section: Figmentioning
confidence: 99%
“…The proof of concept has been shown theoretically by Benedek and Fennie in Ca 3 Mn 2 O 7 [2] where the coupling mechanism with magnetism relies on the improper origin of the polarization that indirectly couples with the magnetization. Unfortunately, the experimental efforts to verify this prediction have, so far, shown that the electric po-larization in Ca 3 Mn 2 O 7 cannot be switched which seems to indicate that this crystal might not be the best candidate for magnetization reversal through an electric field [6]. Following the same strategy, layered materials with formula A n B n X 3n+2 appeared to be other favorable candidates [7][8][9].…”
mentioning
confidence: 99%